The evaluation of heat stress on steel mill workers through monitoring of environmental and acute physiological changes - Hasan, Nurul; Mohd Tamrin, Shamsul Bahri; Syed Ismail, Sharifah Norkhadijah; Abdullah, Ahmad Makmom (American-Eurasian Network for Scientific Information, 2014)
Background: A heat stress problem is one of the physical hazards that encountered tropical countries such as Malaysia. Most of steel mill workers were exposed to hot working condition in a different work process. The effect of heat stress has been identified pose an effect to physiological, health problem and also performance. Objective: The aim of present study was to evaluate the socio demographic factors, environmental factors and physiological factors that contribute to heat stress. Results: The WBGTin indoor during work varied from 26.5°C to 30.6°C. Six out of eight work stations monitored had temperatures regularly exceeded the Threshold Limit Values (TLV). The result also indicate that there was no significant different of systolic blood pressure among the respondents (p>0.05). Changes in heart rate significantly indicate the heat strain among the respondents (P<0.001). The regression analysis suggested monthly income (p<0.001), air velocity (P<0.05), shift work (p<0.001), metabolic rate (p<0.05) and heart rate (p<0.01) were the factors that can contribute to heat stress. Conclusion: The steel mill plant was considered as a hot workplace area since most of their workplaces were exceed the acceptable temperatures, 28.0°C according to American Conference of Governmental Industrial Hygienist (ACGIH) Threshold Limit Value (TLV).